1992
DOI: 10.1111/j.1469-8137.1992.tb01068.x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of inorganic carbon by the coccolithophorid Emiliania huxleyi (Lohmann) Kamptner

Abstract: inorganic carbon-dependent photosynthetic oxygen evolution was saturated at a photon flux density of 100//mol m"^ s"^ for air-grown cells of a low calcifying strain of Emiliania huxleyi (Lohmann) Kamptner. Measurement of photosynthetic oxygen evolution at constant inorganic carbon concentration but varying pH showed that exogenous bicarbonate was not a major carbon source for photosynthesis. At pH 8-0 the concentration of dissolved inorganic carbon (DIC) required for the half-maximal rate of photosynthetic O^ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 23 publications
3
29
0
Order By: Relevance
“…The Rubisco from chlorophyte microalgae has a Km [CO.J in the region of 12 jiM (Jordan & Ogren, 1981) or possibly as low as 9 //M (Yokota & Kitoaka, 1985) but this is under anaerobic conditions and at air-equilibriated oxygen concentrations the K",,., [CO.J is nearer 25 //M. Although the K^^.-^ [CO.,] for low-calcifying cells (Nimer et al, 1992) is lower than the Km [CO.J of Rubisco this does not provide strong support for a ' CO.^-pump' but probably reflects differences in the kinetic parameters of Rubisco from the Prymnesiophyceae compared with the Chlorophyceae. There are essentially two approaches to determine the affinity of an algal cell for CO2 or HCO3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Rubisco from chlorophyte microalgae has a Km [CO.J in the region of 12 jiM (Jordan & Ogren, 1981) or possibly as low as 9 //M (Yokota & Kitoaka, 1985) but this is under anaerobic conditions and at air-equilibriated oxygen concentrations the K",,., [CO.J is nearer 25 //M. Although the K^^.-^ [CO.,] for low-calcifying cells (Nimer et al, 1992) is lower than the Km [CO.J of Rubisco this does not provide strong support for a ' CO.^-pump' but probably reflects differences in the kinetic parameters of Rubisco from the Prymnesiophyceae compared with the Chlorophyceae. There are essentially two approaches to determine the affinity of an algal cell for CO2 or HCO3 .…”
Section: Discussionmentioning
confidence: 99%
“…With a low-calcifying strain of E. huxleyi photosynthetic O2 evolution decreased with increase in pH at constant external inorganic carbon concentration show ing that exogenous bicarbonate was not utilized as a source of inorganic carbon for photosynthesis (Nimer et al, 1992). Studies with a high-calcifying strain revealed a major difference in the pattern of inorganic carbon utilization, in that photosynthetic oxygen evolution increased at alkaline pH there being a 4-fold increase over the pH range 5-8-3 the cells have a high affinity for HCO3" (Fig.…”
Section: Inorganic-carbon-dependent Photosynthetic Og Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown theoretically that growth of E. huxleyi can either decrease the air-sea gradient in pCO 2 driven by 'organic' production or depending on the relative rates of photosynthesis, calcification and respiration, could cause a direct elevation in pCO 2 levels (Crawford and Purdie, 1997;Nimer et al, 1992;Steemann Nielsen, 1966). In addition to the possible production of CO 2 as a result of calcification (Robertson et al, 1994), a reduction in the air-sea pCO 2 gradient at the western end of the transect could also result from the lower rates of carbon fixation in comparison with values observed in the diatom-dominated assemblages to the east.…”
Section: The Biological Implications Of the Bloommentioning
confidence: 99%
“…In h. liuxteyi photosynthetic COj fixation is limited by the avail-Axenic cultures of a low-calcifying strain of ability of CO.^ at ambient levels of DIC (Sikes & Emiliania huxleyi (Lohmann) Kamptner (Scottish Wheeler, 1982), since in the absence of a 'CO.^ Marine Biological Association, no. 279) and a highpump' uptake is by diffusion (Nimer & Merrett, calcifying strain isolated by Dr P. Holligan (Bigelow 1992;Nimer, Dixon & Merrett, 1992). Bicarbonate Laboratory, no.…”
Section: Introductionmentioning
confidence: 99%